Pengaruh Transfer pricing dan Sales Growth Terhadap Tax avoidance Pada Perusahaan di Bidang Teknologi (Data IDX 2021-2023) - Ouduil, Stanley Alberto; Sudjiman, Lorina Siregar; Susanti, Mila (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The global technology sector has experienced significant growth, leading to increased scrutiny of tax practices within companies. Transfer pricing, the practice of setting prices for transactions between affiliated entities, has been a focus of regulatory bodies and academics. The relationship between Sales Growth and Tax Avoidance is an important aspect that has not been explored in the context of technology companies. This research aims to examine the relationship between Transfer pricing, Sales Growth, and Tax Avoidance in the technology industry by utilizing data from the Indonesia Stock Exchange (BEI) from 2021 to 2023. This research uses quantitative methodology, specifically utilizing IDX financial data. for technology companies. Transfer pricing practices will be assessed through financial indicators, while Sales Growth will be measured as a percentage increase in revenue during the research period. Tax Avoidance will be operationalized using predetermined metrics such as effective tax rates. Statistical methods, such as regression analysis, will be used to identify patterns and correlations between variables. Research findings show that there is no relationship between Transfer Pricing and Sales Growth and Tax Avoidance in companies operating in the Technology Sector.